2014
DOI: 10.1080/09602011.2014.941295
|View full text |Cite
|
Sign up to set email alerts
|

Test–retest consistency of Virtual Week: A task to investigate prospective memory

Abstract: The present study reports test-retest consistency of Virtual Week, a well-known measure of prospective memory (PM) performance. PM is the memory associated with carrying out actions at a specific moment in the future. Patients with neurological disorders as well as healthy older adults often report PM dysfunctions that affect their everyday living. In Experiment 1, 19 younger and 20 older adults undertook the standard version of Virtual Week (version A). Older adults showed lower performance compared to younge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 65 publications
3
19
0
Order By: Relevance
“…In addition, the limited differentiation between implementation intentions and rehearsal could have been due to insufficient power. Our pilot study found a larger between-group effect of implementation intentions compared to standard instructions and, similar to a test-retest study of Virtual Week, no practice effect with standard instructions 44 . We increased our sample size to account for the use of an active control condition, but our estimate may have been inadequate.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In addition, the limited differentiation between implementation intentions and rehearsal could have been due to insufficient power. Our pilot study found a larger between-group effect of implementation intentions compared to standard instructions and, similar to a test-retest study of Virtual Week, no practice effect with standard instructions 44 . We increased our sample size to account for the use of an active control condition, but our estimate may have been inadequate.…”
Section: Discussionsupporting
confidence: 83%
“…Of relevance to the current results, there was no difference in Virtual Week performance between testing sessions for the control group (i.e., no apparent practice or learning effect). Further, a test-retest study of Virtual Week with standard instructions in older adults that used the same counter-balanced parallel versions as the current study also showed no practice or learning effect 44 .…”
Section: Methodssupporting
confidence: 57%
“…Thus, all participants involved in Study 2 performed four virtual days, the first two with no strategy and the last two using the future event simulation strategy. In Study 2, participants also performed a recognition task at the end of each virtual day to assess their retrospective memory for the various PM tasks (see Mioni, Rendell, Stablum, et al ., ). Successful PM performance requires executing the intended action at the appropriate moment (i.e., prospective component) as well as remembering the specific action to be performed (i.e., retrospective component) (Einstein & McDaniel, ).…”
Section: Discussion Of Studymentioning
confidence: 97%
“…Participants also have to remember to carry out additional tasks that closely resemble PM tasks in daily life. The version used in this study is the translation and adaptation for the Italian population and includes four virtual days with eight PM tasks per day (Mioni, Rendell, Stablum, Gamberini, & Bisiacchi, 2015;Mioni, Stablum, Biernacki, & Rendell, 2015).…”
Section: Pm Task: Virtual Weekmentioning
confidence: 99%
“…In another study, the split-half reliability for the overall Virtual Week measure was estimated to be: 74 in a clinical group with schizophrenia [73]. In a recent study, test-retest reliability was investigated in older adults by use of the same (Study 1) or parallel (Study 2) versions across two testing time points separate by 1 month [74].…”
Section: Finally Virtualmentioning
confidence: 99%